2021
DOI: 10.1038/s41564-021-00961-5
|View full text |Cite
|
Sign up to set email alerts
|

Microbial signatures in the lower airways of mechanically ventilated COVID-19 patients associated with poor clinical outcome

Abstract: he earliest known case of SARS-CoV-2 infection causing COVID-19 is thought to have occurred on 17 November 2019 (ref. 1 ). As of 3 August 2021, 198.7 million confirmed cases of COVID-19 and 4.2 million deaths have been reported worldwide 2 . As the global scientific community has rallied in a concerted effort to understand SARS-CoV-2 infections, our background knowledge

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
106
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(115 citation statements)
references
References 66 publications
6
106
0
1
Order By: Relevance
“…After evaluating and assessing as much as 257 potential studies, 201 studies were removed due to outcome of interest being not available. In the end, what underlay this meta-analysis were eligible fifty-six articles with 426,261 COVID-19 patients [5] , [6] , [7] , [8] , [9] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] . The detail of selection process is shown by a chart flow in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…After evaluating and assessing as much as 257 potential studies, 201 studies were removed due to outcome of interest being not available. In the end, what underlay this meta-analysis were eligible fifty-six articles with 426,261 COVID-19 patients [5] , [6] , [7] , [8] , [9] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] . The detail of selection process is shown by a chart flow in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Among 164 patients with various types of symptoms, increased abundances of several Prevotella species were among the top predicting taxa from swabs of the posterior oropharynx: P. denticola , P. nigrescens , P. histicola , and P. oulorum in the patient group with ongoing symptoms, and P. denticola , P. melaninogenica , P. jejuni , and P. nigrescens in the determined long-COVID group ( Haran et al, 2021 ). Sulaiman et al (2021) examined a hospitalized cohort of 589 critically ill COVID-19 patients, characterizing their lung microbiome from bronchoalveolar lavage samples. Especially interesting were the findings of two oral commensals, P. oris and Mycoplasma salivarium , among the most dominant, functionally active microbial taxa.…”
Section: Prevotella In Bacterial Communities Of the Respiratory Tractmentioning
confidence: 99%
“…As for COVID-19 pathogenesis, respiratory failure has been associated with increased mortality, and one study showed that in the lungs, SARS-CoV-2 load, anti-SARS-CoV-2 antibody responses and the microbiota are predictive of poor outcomes in patients who are severely ill with COVID-19 (ref. 2 ). With regards to therapeutics, one in vivo study in ferrets reported prophylactic and infection-limiting efficacy for a promising oral SARS-CoV-2 antiviral, molnupiravir 3 , which is currently in phase 2/3 clinical trials (NCT04575597).…”
mentioning
confidence: 99%